MiR-526b-3p Attenuates Breast Cancer Stem Cell Properties and Chemoresistance by Targeting HIF-2α/Notch Signaling - Jing-Hua Liu; Wen-Ting Li; Yue Yang; Yan-Bo Qi; Yu Cheng; Jia-Hui Wu (Frontiers in Oncology, 2021)
Chemoresistance is a severe clinical challenge in breast cancer. Hypoxia and cancer stem cells (CSCs) contribute to the paclitaxel (PTX) resistance, but the molecular mechanisms are still elusive. MicorRNAs (miRNA) have been considered a promising therapeutic strategy in various cancers. Here, we identified the crucial function of miR-526b-3p in regulating PTX resistance and CSC properties. Our data demonstrated that miR-526b-3p mimic repressed the cell viability of breast cancer cells. The counts of Edu-positive cells were reduced by miR-526b-3p in breast cancer cells. Meanwhile, the apoptosis of breast cancer cells was induced by miR-526b-3p. Tumorigenicity analysis in the nude mice confirmed that miR-526b-3p attenuated the breast cancer cell growth in vivo. Significantly, hypoxia could enhance IC50 value of PTX in breast cancer cells. IC50 value of PTX was induced in breast cancer mammospheres. The hypoxia-inducible factor 2α (HIF-2α) expression was enhanced, but miR-526b-3p expression was repressed under hypoxia in breast cancer cells. Also, breast cancer mammospheres presented high HIF-2α expression and low miR-526b-3p expression. The inhibition of miR-526b-3p enhanced the IC50 value of PTX in breast cancer cells. MiR-526b-3p inhibitor enhanced the colony formation counts of PTX-treated breast cancer cells. The treatment of miR-526b-3p mimic suppressed the sphere formation counts of breast cancer cells and inhibited ALDH1 and Nanog expression. MiR-526b-3p was able to target HIF-2α in the cells. The overexpression enhanced but miR-526b-3p reduced the IC50 value of PTX in breast cancer cells, in which the overexpression of HIF-2α could rescue the miR-526b-3p-inhibited IC50 value of PTX. Overexpression of HIF-2α reversed miR-526b-3p-regulated apoptosis, colony formation ability, and ALDH1 and Nanog expression in the cells. Interestingly, the overexpression of HIF-2α induced but miR-526b-3p repressed the expression of HIF-2α, Hey2, and Notch in PTX-treated breast cancer cells, while HIF-2α could reverse the effect of miR-526b-3p. In conclusion, miR-526b-3p attenuated breast cancer stem cell properties and chemoresistance by targeting HIF-2α/Notch signaling. MiR-526b-3p may be utilized in the relieving chemoresistance in breast cancer.